Biomechanical Evaluation of the CD HORIZON Spire Z Spinal System With Pedicle and Facet Fixation. Issue 15 (1st August 2016) - Godzik, Jakub; Kalb, Samuel; Martinez-del-Campo, Eduardo; Newcomb, Anna G.U.S.; Singh, Vaneet; Walker, Corey T.; Chang, Steve W.; Kelly, Brian P.; Crawford, Neil R.
Abstract : Study Design: Human cadaveric biomechanical study. Objective: The aim of this study was to evaluate the biomechanics of lumbar motion segments instrumented with the CD HORIZON Spire Z plate system (Spire Z), a posterior supplemental fixation spinous process plate, alone and with additional fixation systems. Summary of Background Data: Plates and pedicle screw/rod and facet screw implants are adjuncts to fusion. The plate limits motion, improving segmental stability and the fusion microenvironment. However, the degree to which the plate contributes to overall stability when used alone or in conjunction with additional instrumentation has not been described. Methods: Standard nondestructive flexibility tests were performed in 7 L2–L5 human cadaveric spines. Spinal stability was determined as mean range of motion (ROM) in flexion/extension, lateral bending, and axial rotation. Paired comparisons were made between five conditions: (1) intact/control; (2) Spire Z; (3) Spire Z with unilateral pedicle screw/rod system (Spire Z+UPS); (4) Spire Z with unilateral facet screw system (Spire Z+UFS); and (5) Spire Z with bilateral facet screw system (Spire Z+BFS). Stiffness and ROM data were compared using one-way analysis of variance, followed by repeated-measures Holm-Šidák tests. Results: Spire Z was most effective in limiting flexion (20% of normal) and extension (24% of normal), but less effective in reducing lateral bending and axial rotation. In lateral bending, Spire Z+BFS and Spire Z+UPS constructs were not significantly different and demonstrated greater ROM reduction compared with Spire Z+UFS and Spire Z ( P  < 0.001). Spire Z+BFS demonstrated greatest stiffness in axial rotation compared with Spire Z+UPS ( P  = 0.025), Spire Z+UFS ( P  = 0.001), and Spire Z ( P  < 0.001). Spire Z+UPS was not significantly different from Spire Z+UFS ( P  = 0.21), and superior to Spire Z ( P  = 0.013). Conclusion: The Spire Z spinous process plate provides excellent immediate fixation, particularly for flexion and extension. While the hybrid Spire Z+BFS screw construct afforded the greatest stability, Spire Z+UPS demonstrated considerable promise. Level of Evidence: N/A